Role of Evaluating MGMT Status and 1p36 Deletion in Radiosurgery-Induced Anaplastic Ependymoma That Rapidly and Completely Resolved by Temozolomide Alone: Case Report and Review of the Literature - Hirono, Seiichiro; Iwadate, Yasuo; Kambe, Michiyo; Hiwasa, Takaki; Takiguchi, Masaki; Nakatani, Yukio; Saeki, Naokatsu (Journal of Neurological Surgery Reports, 2015)
Stereotactic gamma knife surgery (GKS)-induced brain tumors are extremely rare, and no ependymal tumors induced by GKS have been reported. Therefore, little is known about their clinical, pathologic, and genetic features. In addition, a regimen of adjuvant chemotherapy for anaplastic ependymoma (AE) has not been established. A 77-year-old man presented with a gait disturbance and left-side cerebellar ataxia more than 19 years after GKS performed for a cerebellar arteriovenous malformation. Imaging studies demonstrated an enhancing mass in the irradiated field with signs of intraventricular dissemination. Surgical resection confirmed the diagnosis of AE. Temozolomide (TMZ) was administrated postoperatively because the methylated promoter region of O6-methylguanine-DNA methyltransferase (MGMT) and 1p36 deletion were observed. Surprisingly, images 16 days after TMZ initiation demonstrated a complete resolution of the residual tumor that was maintained after three cycles of TMZ. This first case report of GKS-induced AE emphasizes the importance of genetic evaluation of MGMT and chromosomal deletion of 1p36 that are not commonly performed in primary ependymal tumors. In addition, it is speculated that a GKS-induced tumor may have a different genetic background compared with the primary tumor because the pathogenesis of the tumors differed.
Keywords: anaplastic ependymoma; radiosurgery; MGMT; 1p36; temozolomide